Asset Effects in Land Price Formation in Agriculture: The Evidence from South Asia (The Pakistan Development Review, 1996)
The purpose of this paper is to examine the land market behaviour in South Asia, taking the most technologically advanced Punjab (both Pakistan and India) as an example, and to consider the disparity issues in development. Land market in Punjab was given momentum when the private proprietorship of land was established in the middle of the 19th century. Land market behaviour in terms of the rentland price ratio or the profitability of investment in land cannot be explained by the conventional rent theory. Land price has never been the discounted value of rent. We try to explain the market behaviour by incorporating asset effects in addition to the technological effects in agricultural production. Since the land price data are not published after independence both in Pakistan and India, it is difficult to confirm whether or not the observed trend of declining rent-land price ratio can be observed after independence. However, judging from the scattered field survey data, we could presume that the asset effects have been positive and increasing, thereby reducing the R/P ratio much lower than the market interest rate. The study raises questions with respect to the direction of public investment, land tax policy, and the growing disparity between rent receivers and rent payers.